2019
DOI: 10.1051/matecconf/201928901002
|View full text |Cite
|
Sign up to set email alerts
|

Production of concrete compatible biogranules for self-healing concrete applications

Abstract: Recently, cost-efficient nitrate reducing biogranules were suggested as an alternative to axenic microbial cultures for development of microbial self-healing concrete. In a marine environment, biogranule containing microbial self-healing concrete showed simultaneous self-healing of cracks and immunisation against rebar corrosion. Yet, information about the production strategy of these biogranules and their compatibility with a mortar matrix is limited. This study presents the production of biogranules and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…ACDC biogranules were obtained successfully and quality assessment revealed that the properties were similar to those produced in previous studies (data not shown, can be found in [13]). Obtained granules are visually represented in Figure 1.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…ACDC biogranules were obtained successfully and quality assessment revealed that the properties were similar to those produced in previous studies (data not shown, can be found in [13]). Obtained granules are visually represented in Figure 1.…”
Section: Resultssupporting
confidence: 74%
“…After 60 days of operation, the first batch of biogranules were harvested and dried in a ventilated electric oven at 60ºC for 48 hours. These granules were fresh new ACDC granules cultivated from old dry ACDC granules and revealed similar properties [13]. Upon drying, granules were further allocated into three portions based on their particle sizes (0.45 to 2 mm) and stored in closed containers at room temperature.…”
Section: Materials and Methods 21 Self-protected Biogranules As Microbial Healing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the studies on the cultivation of self-protected bio granules by Sonmez and Ersan (2019) proved that the activated compact denitrifying core, ACDC bio granules do not have any impact on the strength development and are compatible with hardened mortar [ 106 ]. In their experiment, bio granules with activated denitrifying core were used in tested bio-mortar mixtures as a microbial agent.…”
Section: Self-healing Polymers In Construction Applicationmentioning
confidence: 99%
“…In addition, accurate and exact survival determination can provide insight into the protective abilities of the capsule material and possibly the self-healing behavior the capsule offers (i.e., if healing agents are retained in the capsule or leached into the cement environment). While metabolic measurements such as the urea consumption (the TAN method) for ureolytic bacterial [ 28 , 45 ] and NO 3 − /NO 2 − consumption measurements for non-ureolytic NO 3 − /NO 2 − metabolizing bacteria [ 4 , 29 , 46 , 47 , 48 , 49 , 50 ] can be considered reliable measurements for bacterial survival and activity, while direct and accurate bacteria survival measurements are limited for non-ureolytic bacteria that do not metabolize NO 3 − /NO 2 − , e.g., those who oxidize organic salts. Since this class of non-ureolytic bacteria are the most prevalent in non-ureolytic concrete self-healing research, there is a need for better quantitative survival measurement strategies for such systems.…”
Section: Introductionmentioning
confidence: 99%